2016
DOI: 10.18632/oncotarget.10326
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin triggers autophagic cell survival which drives epithelial mesenchymal transition and chemoresistance in bladder cancer cells in an Hedgehog-dependent manner

Abstract: Bladder cancer (BC) is a common urologic tumor characterized by high risk of recurrence and mortality. Capsaicin (CPS), used as an intravesical drug for overactive bladder, was demonstrated to induce cell death in different cancer cells including BC cells.Here we found that treatment of high-grade BC cells with high dose of CPS triggers autophagy. Infact, the CPS treatment alters the redox homeostasis by inducing production of radicals, mitochondrial depolarization, alterations of ADP/ATP ratio and activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 53 publications
(61 reference statements)
1
45
0
Order By: Relevance
“…220 When the Hh ligand is present, it binds to PTCH, which changes the spatial conformation of PTCH, removing the inhibition of SMO activating the transcription factor GLI and inducing it to enter the cell nucleus, where GLI regulates cell growth, proliferation, and differentiation. 221 Studies have confirmed that abnormal activation of the Hh signaling pathway can be found in human cancers, 222 such as breast cancer, 223 lung cancer, 224 bladder cancer, 225 pancreatic cancer, 226 chondrosarcoma, 227 rhabdomyosarcoma, 228 neuroblastoma, 229 medulloblastoma, 230 and gastric cancer. 231 However, activation of Hh signaling is different in different tumors.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 92%
“…220 When the Hh ligand is present, it binds to PTCH, which changes the spatial conformation of PTCH, removing the inhibition of SMO activating the transcription factor GLI and inducing it to enter the cell nucleus, where GLI regulates cell growth, proliferation, and differentiation. 221 Studies have confirmed that abnormal activation of the Hh signaling pathway can be found in human cancers, 222 such as breast cancer, 223 lung cancer, 224 bladder cancer, 225 pancreatic cancer, 226 chondrosarcoma, 227 rhabdomyosarcoma, 228 neuroblastoma, 229 medulloblastoma, 230 and gastric cancer. 231 However, activation of Hh signaling is different in different tumors.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 92%
“…It has been implicated in tumor growth and progression and explored as a potential therapeutic target [ 26 , 27 ]. Recently, a role for autophagy in capsaicin-induced cell death was proposed following reports indicating that capsaicin may induce autophagy, suggesting a promising therapeutic strategy for cancer [ 21 , 28 , 29 , 30 ]. However, only a few studies have examined capsaicin-induced apoptosis of NPC cells, and the effects of capsaicin on autophagic-associated pathways in NPC remain questionable.…”
Section: Introductionmentioning
confidence: 99%
“…High doses of capsaicin induce autophagy, apoptosis, and inhibition of autophagy sensitized capsaicin-induced apoptosis in bladder [41] and liver cancer cells [42]. Although the autophagic parameters were not measured in the current study, autophagy could be considered as a potential mechanism of capsaicin's anti-cancer activity in human colon cancer cells.…”
Section: Anti-tumorigenic Effects Of Capsaicin In Colon Cancermentioning
confidence: 74%